Navigating the divide: inequalities in household experiences of healthcare disruption in Latin American and the Caribbean countries amidst COVID-19 - Cristian A. Herrera; Amanda C. Kerr; Julia Dayton Eberwein; Paula Bedregal; Dionne Kringos; Niek Klazinga (BMC, 2024)
Abstract Background Latin America and the Caribbean (LAC) is among the most unequal regions in the world in terms of wealth and household income. Such inequalities have been shown to influence different outcomes during the COVID-19 pandemic, including the disruption of routine health services. The aim of this paper is to examine socioeconomic inequalities in household experiences of healthcare disruption in LAC countries from mid-2020 to late 2021. Methods We used household-level data from the COVID-19 High Frequency Phone Surveys (HFPS), conducted in 14 LAC countries in one round in 2020 and 24 countries in two rounds in 2021. Ordinary least square and Logit multivariate regressions were conducted to examine the correlation between reported healthcare disruptions with household characteristics for 2020 and 2021. Since household income levels were not directly collected in the HPFS, we created an index of inequality and estimated the relative index of inequality. Results When analyzing 2020-2021 together, reported healthcare disruptions were lower if the respondent was employed or did not report lack of food in the last month; if the household had more people aged 65 or older or more rooms to sleep in. When analyzed separately in 2020 and 2021, having more people aged 65 or older or not experiencing food insecurity remained stable factors for lower odds of disruption in both years. In addition, being employed was associated with lower odds of disruption in 2020, while being male or having more rooms to sleep in were associated with lower odds of disruption in 2021. Regarding wealth differences in 2021 (it was not possible to compute it for 2020), households with the lowest wealth were 27.3% more likely to report a care disruption than households with the highest wealth. Conclusions The socioeconomic status of households in LAC was a relevant factor in explaining the disruption of healthcare during the COVID19 pandemic, with a clear social gradient where the wealthier a household, the less likely it was to experience disruption of care. Food security, employment, and gender policies should be integral to preparing for and responding to future shocks such as pandemics. Prioritizing the most affected populations, like the elderly during COVID-19, can enhance the health system effectiveness.